Structural analysis and recent tectonics in the central Alboran Sea - Martínez-García, P.; Soto, J. I.; Comas, M. (TRABAJOS DE GEOLOGÍA, 2010)
We analyze the distribution and character of recent deformations in the Alboran Ridge andneighbouring areas of the Alboran Sea (within the Gibraltar Arc System, in the WesternMediterranean). Shallow structure has been analyzed by integrating different geophysical datasets, suchas multibeam swath-bathymetry and sub-bottom profiling and comparing with deeper sections shownin multichannel seismic profiles. We explore relationships between upper-crustal structures and shallowseismicity, to decipher the position and nature of active fault segments. Pliocene to recent uplift ofthe Alboran Ridge has been produced by reverse to strike-slip faulting along NE-SW trending faultsystemsthat show a transpressive character. Major faults bounding the ridge gradually change theirdirection from NE-SW to NW-SE and connect with the transtensional Yusuf fault system, whichincludes the Yusuf Ridge and Basin. Towards the west, the ridge is affected by NNE-SSW trendingfolds, associated with high-angle faults at depth. These structures define a seismogenic, left-lateral faultzone connected to the south with the Al Hoceima seismic swarm.